1995
DOI: 10.1002/j.2161-007x.1995.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Client Religious Beliefs and Practices in the Education of Counselors in CACREP‐Accredited Programs

Abstract: Responses by heads of CACREP‐accredited programs to a survey indicate that client religious beliefs are considered to be important curricular components in just over half of the programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 4 publications
3
48
0
Order By: Relevance
“…Although only 22% of respondents indicated that their program had a specific course dealing with spirituality, 69% reported that their program addressed these issues within the curriculum. This is an increase in the number of programs that report addressing spirituality and religion compared with previous research (i.e., Kelly, 1997;Pate & High, 1995). Nevertheless, it remains unclear how spirituality and religion are addressed in these programs.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Although only 22% of respondents indicated that their program had a specific course dealing with spirituality, 69% reported that their program addressed these issues within the curriculum. This is an increase in the number of programs that report addressing spirituality and religion compared with previous research (i.e., Kelly, 1997;Pate & High, 1995). Nevertheless, it remains unclear how spirituality and religion are addressed in these programs.…”
Section: Resultsmentioning
confidence: 88%
“…In recent years, researchers have found that about half of accredited counseling programs reported including spiritual and religious issues as part of training (Kelly, 1997;Pate & High, 1995), which makes the results of this study interesting for several reasons. First, this study provides empirical support for the inclusion of spiritual and religious knowledge competencies in counselors' training because respondents tended to show moderately strong agreement that the competencies under investigation are important for effective preparation of counselors-in-training.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The thrust of the research in this area is on incorporating religious and spiritual variables in practitioner education (Kelly Jr., 1994); or the need for practitioners to develop competencies to work with religious and spiritual issues in counselling (Pate Jr. & High, 1995); highlighting the benefits to clients. The conclusion from most research in this area highlights the fact that despite the importance of religion/spirituality in most clients' lives, practitioners are not given adequate training to prepare them to deal with issues arising in these realms (Delaney, et al, 2007;Shafranske & Malony, 1990).…”
Section: Including Spirituality In the Training Processmentioning
confidence: 99%